If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x + 35 - 14x = 26x + 35
We simplify the equation to the form, which is simple to understand
2x+35-14x=26x+35
We move all terms containing x to the left and all other terms to the right.
+2x-14x-26x=+35-35
We simplify left and right side of the equation.
-38x=0
We divide both sides of the equation by -38 to get x.
x=-0
| 7x+3=7(x-4) | | 0.31+0.15(x-1)+2.12=2.73 | | 8x^7-40x^5=0 | | 4h-10=2h-4 | | 5g+2(-3+3g)=1-g | | 4(6x-30)=72 | | f(5+5)=f(5)+f(5) | | 10y=7y+21 | | x^2+y^2=90 | | 2(11+2x)+2(19+2x)=76 | | (x+4)2+112=0 | | f(5+5)= | | abs(10+2x)=16 | | -6X+-36+2=-6x+-3 | | x^2+(x+8)=40 | | 2(5x+6)=10x | | 45-48x=30x+40 | | 3a-5=(-14) | | 4(r+6)+36=2(2r+40) | | 8j-5=46 | | 60+50.45x=0+57.95 | | 9+4x=428 | | 7y-15=-1 | | y-9=-5(x+6) | | 3(9y+3)-11=2y+21 | | -6X+-36=-6x+-3 | | 2x+(3+4)=52 | | ax+d=c-bx | | 60n=(-12) | | -6X+36+2=-6x+-3 | | x+b=c-z | | 9a-(-72)=-8 |